GOOD OUTCOME FOR VERY HIGH RISK ADULT B-CELL ACUTE LYMPHOBLASTIC LEUKAEMIA CARRYING GENETIC ABNORMALITIES t(4;11)(q21;q23) or t(9;22)(q34;q11), IF PROMPTLY SUBMITTED TO ALLOGENEIC TRANSPLANTATION, AFTER OBTAINING A GOOD MOLECULAR REMISSION. - Matteo Parma; Clara Vigano'; Monica Fumagalli; Federica Colnaghi; Arianna Colombo; Federica Mottadelli; Vincenzo Rossi; Elena Elli; Elisabetta Terruzzi; Angelo Belotti; Giovanni Cazzaniga; Enrico Maria Pogliani; et al. (Mediterranean Journal of Hematology and Infectious Diseases)
Background and Objectives: Acute lymphoblastic leukaemia (ALL) carrying t(9;22) or t(4;11) genetic abnormalities represents a very high risk subtype of disease (VHR-ALL). Hematopoietic stem cell transplantation (HSCT) still remains the only curative option also in the Imatinib era. In the last years low molecular level of minimal residual disease (MRD) before HSCT was reported as one of the best favourable indexes for survival in ALL. Here we observed that even these patients can show a favourable outcome, if submitted to HSCT with very low MRD. Methods: We considered 18 consecutive VHR-ALL patients eligible to HSCT. 16 of them were transplanted upon first remission, as soon as possible, employing myelo-ablative conditioning regimens. Molecular MRD has been evaluated before and after HSCT.Results: Immediately before HSCT MRD revealed: complete molecular remission (MRDneg) for 5 patients and a level <1x10-3 for 7 patients; 100 days after HSCT we had: MRDneg for 7 patients and a decrease for all the others after HSCT. After tapering of immunosuppressive drugs, 13 patients reached the MRDneg in a median time of 8 months (range 3-16); Based on intention to treat analysis: 14/18 patients are alive and disease free at the time of analysis, overall survival and event free survival is of 78% and 66% respectively, with an average follow-up of 45 months (range 6-84) since HSCT. Conclusion: Early transplantation with low MRD level seems to be correlated with a favourable outcome also in VHR-ALL